Experiments on tsunami induced boulder transport - a review - Oetjen, Jan; Engel, Max; Schüttrumpf, Holger (Earth science reviews, 2021)
The interest in applying coastal boulders as a proxy for high-energy wave events, i.e., tsunamis and major storms, increased significantly during the last two decades. Studies include on-site investigations, numerical modelling or experimental studies. However, inferences on past inundation processes based on commonly used inverse modelling approaches are associated with significant uncertainties and the need for validation of relevant parameters has been expressed. Here, we review experimental studies on the transport of natural boulders (and artificial bodies) by tsunamis, which provide crucial insights into the physical parameters controlling the transport process. We summarize and categorize the differences and scopes of existing experimental studies and point out the importance of the boulders' wave-facing area and, thus, the drag force, which is highlighted in most studies. The boulder-transport mode (e.g., rolling or sliding), however, varies strongly throughout the publications. A considerable number of influencing parameters is not investigated systematically (e.g., the influence of boulder-boulder interactions) so far, and there is an agreement that existing hydrodynamic equations for mobilization thresholds tend to overestimate the necessary wave height and velocity due to the existing uncertainties. Therefore, and based on the current knowledge, working with parameter ranges (e.g., mobilization thresholds, transport-distance spans) is recommended instead of using exact values. However, we demonstrate that comparisons of the particular findings of the reviewed studies is not straightforward due to very individual experimental setups. Based on this, we propose a standardized research environment, which might simplify the knowledge transfer between studies and can possibly improve numerical models for tsunami-induced boulder transport.
Gesehen am 17.11.2021